Performance Analysis of Islamic Commercial Banks for the Period 2017-2021. - Kurniawan, Muhammad Rifki; Sadeli; Utomo, Humam Santosa (International Journal of Islamic Finance, 2023)
Banking has a significant influence on the economic activities of a country. The banking sector in Indonesia is currently experiencing rapid growth. One of the banks that is growing rapidly is Islamic banking. The development of Islamic banking must demonstrate sufficient performance in building trust among shareholders in their investments. To achieve this trust, it is necessary to measure the performance of Islamic banks, hence the need for a tool that can evaluate and measure the performance of these Islamic banks. The assessment of the financial performance of Islamic banks not only focuses on financial aspects but also requires an evaluation of their performance in accordance with Sharia principles to build trust among stakeholders. This research aims to determine the performance level of registered Islamic commercial banks in the financial services authority using the Islamicity Performance Index and RGEC methods for the years 2017-2021. This type of research is descriptive research with a quantitative approach. Data were obtained through documentation techniques. Data analysis techniques utilized the Islamicity Performance Index and RGEC methods. This research introduces novelty in its research methodology. Many studies typically focus on a single method, while this research employs two methods simultaneously. Additionally, this study utilizes the most recent data. The type of research is descriptive research using a non-statistical quantitative approach. The data used in this study are secondary data. The data collection technique in this research is the documentation method. The sampling technique in this study is non-probability sampling. The data analysis technique in this research involves descriptive statistical analysis using the Islamicity Performance Index and RGEC methods. The research results indicate that the assessment of the performance level of Islamic commercial banks using the Islamicity Performance Index method for the years 2017-2021 falls under the category of less satisfactory in terms of spirituality. The values for the respective years were 2.375, 2.375, 2.5, 2.5, and 2.625. The evaluation of the performance of Islamic commercial banks using the RGEC method in 2017 showed that the banks' performance was in Composite Rank 3 (PK-3) with a score of 66.67%, indicating a moderately healthy category. Meanwhile, for the years 2018-2021, the performance of the banks was in Composite Rank 2 (PK-2) which falls under the healthy category, with scores of 80%, 80%, 76.67%, and 76.67% respectively. The suggestions from this research are that Islamic commercial banks should be able to improve the company's profits, zakat, dividend distribution, and qard & donation. The banks are also expected to enhance their effectiveness in obtaining company profits, as some banks are still experiencing negative profit values. Subsequent researchers are encouraged to conduct further research, including accuracy testing on the Islamicity Performance Index and RGEC methods.